The Effect of Taxation Understanding on Tax Reporting Compliance in MSMEs in South Lampung Regency - Nofitasari, Susi; Tomy, Chairian (Universitas Indonesia Mandiri, 2025)
This study aims to analyze the effect of taxation understanding on tax reporting compliance among Micro, Small, and Medium Enterprises (MSMEs) in South Lampung Regency. It employs a descriptive and quantitative approach using primary data obtained through surveys. The results indicate that a higher level of taxation understanding significantly enhances tax reporting compliance. However, challenges such as limited access to taxation information and education remain significant issues. This research provides insights and understanding to improve tax education programs to support MSMEs in fulfilling their tax obligations more effectively.